Malnutrition among 3 to 5 Years Old Children in Baghdad City, Iraq: A Cross-sectional Study (Journal of Health, Population and Nutrition, 2013)
The unstable geopolitical situation in Iraq since 2003 still affects the health of people, especially children. Several factors may indirectly affect a childs nutritional status. The main aim of this study was to identify factors contributing to malnutrition among 3 to 5 years old children in Baghdad city, Iraq. Two hundred twenty children aged 3 to 5 years were chosen randomly from four kindergartens in Baghdad city according to the cross-sectional design. The nutritional status of the children was assessed using a weight-for-age z-score based on the World Health Organization 2007 cutoff points, in which any child with a z-score of